2015
DOI: 10.1016/j.jgeb.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Bacillus thuringiensis isolates from Egyptian soils as shown by molecular characterization

Abstract: Different techniques were adopted for molecular characterization of several indigenous strains of Bacillus thuringiensis (Bt) previously isolated from Egyptian soil samples. These isolates show different toxicity levels against neonate larvae of both insect species; Spodoptera littoralis (Biosduval); and Helicoverpa armigera (Hübner). The parasporal crystals among the most potent isolates contained polypeptides of about 127 and 130 kDa. PCR screening for genes encoding different Cry genes was performed. The Cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
4
7
0
3
Order By: Relevance
“…Totally, the findings of the present study are similar to those presented by Bravo et al (1998) who reported that the most abundant gene was cry1 among the Mexican strains collected from soil samples. Compatible to our results, characterization of the strains isolated from Egyptian soil samples clarified that 77.77% of them contained the cry1C genes (Salama et al, 2015). Similar to the present study, Yilmaz et al (2012) found that cry1A along with cry1C from the most pathogenic Bt strain (SY49.1) collected from Turkey.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Totally, the findings of the present study are similar to those presented by Bravo et al (1998) who reported that the most abundant gene was cry1 among the Mexican strains collected from soil samples. Compatible to our results, characterization of the strains isolated from Egyptian soil samples clarified that 77.77% of them contained the cry1C genes (Salama et al, 2015). Similar to the present study, Yilmaz et al (2012) found that cry1A along with cry1C from the most pathogenic Bt strain (SY49.1) collected from Turkey.…”
Section: Discussionsupporting
confidence: 90%
“…Although, the 1013 and 1019 isolates were collected from different provinces, they showed the same pattern and produced one band. Due to genetic diversity observed in the Bt strains and containing more than one cry gene located on the plasmids or chromosomes, polymerase chain reaction (PCR) can be a precise procedure to discover and characterize the genes (Salama et al, 2015). In the present study, all isolates exhibited bands of the expected size for cry1A, and few ones showed the expected bands for cry1Aa.…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, Salekjalali et al (2012) identified isolates harboring different cry -type genes through PCR and found 47% of the strains amplified with the cry1 primer, 29% with cry3 and 13% with cry4. Salama et al (2015) reported that cry 1 gene is the most abundant in these isolates (83.33%) among tested cry -type genes, followed by cry 1 gene subfamilies ( cry1B and cry1C ) with percentage of 38.88 and 77.77%, respectively. The tested isolates showed the presence of cry2A gene, but not all of these isolates were positive for cry 2 gene (55.55%).…”
Section: Resultsmentioning
confidence: 94%
“…Similarly, Prabagaran et al (2002) reported the presence of cry1 genes in different indigenous Bt strains potentially active against S. litura. Reddy et al (2013) have reported a novel SARKAR AND KALA native Bt strains isolated from different habitats (Salama et al 2015, Jain et al 2017. cry1I and cry2 genes were present in only one strain each and that too in combination with cry1A (VKK-SO) and cry1A+cry1D (VKK-AC1) respectively.…”
Section: Resultsmentioning
confidence: 99%